PEMBELAJARAN KONSEP BILANGAN DI KELAS RENDAH: TANTANGAN, STRATEGI, DAN PERAN MEDIA PEMBELAJARAN - Fina Juliani; Nurhaswinda; Bella Novita; Farla Fitri Ramadhani; Afnida Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning number concepts in lower grades (grades 1-3) serves as the primary foundation in elementary school mathematics education. This study aims to analyze the challenges, strategies, and role of learning media in helping students in grades 1-3 develop a deep understanding of number concepts. A descriptive literature review approach was employed by analyzing relevant research from 2016 to 2026. The findings indicate that lower grade students frequently face difficulties in understanding place value, number symbols, and basic arithmetic operations. Contributing factors include limited learning media, teacher-centered methods, and insufficient opportunities for concrete hands-on experiences. The use of manipulative media such as number bags, number cubes, and natural materials has been shown to significantly improve students' conceptual understanding and learning motivation. Contextual approaches that connect number concepts to students' real-life experiences also positively impact engagement and academic outcomes. This article recommends enhancing teachers' competency in selecting and developing innovative learning media and promoting school-level policies that support the provision of adequate learning resources.